The legislation approach of the third party liability insurance for construction designers and contractors - Keršuliene, Violeta (Technological and Economic Development of Economy, 2005)
Compulsory Third Party Liability Insurance is ranked as one of the most risky kinds of insurance. In the course of introducing the compulsory Third Party Liability Insurance for construction designers and contractors in Lithuania the experience of foreign countries was used for setting the insurance object, the criteria for the insured events and the third party rights for insisting on liability (restitution) for damages. The article analyses the provisions of law of construction and by‐laws regulating compulsory Third Party Liability Insurance for construction designers and contractors as well as the object of the compulsory Third Party Liability Insurance and differences between the compulsory and voluntary Third Party Liability Insurance for construction designers and contractors have been outlined. The evidence and conditions of the insured events within the Third Party Liability Insurance are reviewed and the insured event has been distinguished from a number of other events. Article in Lithuanian. Statinio projektuotojų ir rangovų privalomojo civilinės atsakomybės draudimo teisinio reglamentavimo aspektai Santrauka. Civilines atsakomybės draudimas priskiriamas prie rizikingiausių draudimo rūšių. Lietuvoje įvedus privalomąjį statinio projektuotoju ir rangovų civilines atsakomybės draudimą, buvo pasinaudota užsienio šalių patirtimi nustatant draudimo objektą, draudiminio įvykio kriterijus, trečiųjų asmenų teisę tiesiogiai reikalauti atlyginti žala. Straipsnyje nagrinėjamos Lietuvos Respublikos statybos įstatymo nuostatos ir poįstatyminiai teisės aktai, reglamentuojantys privalomąjį projektuotojo ir rangovo civilinės atsakomybės draudimą, analizuojamas privalomojo civilinės atsakomybės draudimo objektas, skirtumai tarp privalomojo ir savanoriškojo statinio projektuotojo ir rangovo civilines atsakomybės draudimo. Apžvelgiami privalomojo civilinės atsakomybės draudimo draudiminio įvykio požymiai, sąlygos, bandoma išskirti draudiminį įvykį iš kitų įvykiu. Reikšminiai žodžiai: civiline atsakomybė, privalomasis draudimas, statinio projektuotojas, rangovas, draudiminis įvykis, draudimo rizika. First Published Online: 21 Oct 2010